2008
DOI: 10.1016/j.ejcts.2007.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Esmolol before 80min of cardiac arrest with oxygenated cold blood cardioplegia alleviates systolic dysfunction. An experimental study in pigs☆

Abstract: Objective: Myocardial dysfunction after reperfusion can be a clinical problem in the early postoperative phase after on-pump cardiac surgery. The aim was, in an experimental setting, to investigate if administration of the b-adrenergic receptor blocker esmolol prior to cross-clamping for 80 min with cold oxygenated blood cardioplegia would improve myocardial protection and early postoperative function. Methods: Twenty-four anaesthetised pigs were randomly allocated into one of two equally sized groups and put … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The mechanisms of myocardial protection of beta-blockers in CABG are not yet fully understood. Animal experiments suggest that beta-blockade is cardioprotective during reperfusion, either by reduction in infarct size, improvement of ventricular function, reduction in apoptosis or decrease of myocardial edema [ 9 , 10 ] . The possible mechanisms involved in this protection include reducing the release of oxygen free radicals and adhesion to endothelium nuclear polymorphs (major source of inflammatory response) [ 11 ] .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of myocardial protection of beta-blockers in CABG are not yet fully understood. Animal experiments suggest that beta-blockade is cardioprotective during reperfusion, either by reduction in infarct size, improvement of ventricular function, reduction in apoptosis or decrease of myocardial edema [ 9 , 10 ] . The possible mechanisms involved in this protection include reducing the release of oxygen free radicals and adhesion to endothelium nuclear polymorphs (major source of inflammatory response) [ 11 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Others have investigated the potential for beta‐blockers to enhance the efficacy of cardioplegia, based on evidence that these agents are beneficial in ischaemic heart disease . There has been particular interest in the beta‐blocker esmolol, as its short elimination half‐life (9 mins) would minimize prolonged negative inotropic effects expected with conventional beta‐blockers . Indeed, arrest with esmolol alone has been shown experimentally to protect from damage induced by cardioplegia and esmolol pre‐treatment improves outcomes in the pig cardiopulmonary bypass model .…”
Section: Pharmacologic Agents In Cardioplegia In Pre‐clinical Models mentioning
confidence: 99%
“…53 Indeed, arrest with esmolol alone has been shown experimentally to protect from damage induced by cardioplegia 54,55 and esmolol pre-treatment improves outcomes in the pig cardiopulmonary bypass model. 53 A more recent study has shown that use of a blood-based cardioplegic solution supplemented with esmolol improves both pre-load recruitable stroke work and the cardiac index in a pig bypass model compared to cardioplegia alone (Table 3). 56 Thus, beta-blockers appear to enhance recovery of function following cardioplegia.…”
Section: Other Pharmacological Strategiesmentioning
confidence: 99%
“…Also, cardioplegia contained esmolol, an ultra-short acting (9-minute half-life) cardioselective beta blocker [3], has cardioprotection in animal model and clinical patients [4-7]. However few studies have investigated beta-adrenergic antagonist on the details of the cardiac recovery and rhythm during CPB.…”
Section: Introductionmentioning
confidence: 99%